Democracy and Europe's Crisis of Legitimacy - Stefan Collignon (Intervention. Zeitschrift fuer Ökonomie / Journal of Economics, 2006)
First paragraph: The European Union is in a state of profound crisis. The way it responds to its current situation will determine whether the European dream can survive. The failed ratification of the Constitutional Treaty first revealed the crisis. The European Council meeting in June 2005 then aggravated it, when the heads of state and government failed to agree on a financial framework for the EU budget over the next seven years. Although a compromise was stitched up in December, the European Parliament has rejected it as insufficient. Without the financial means to implement policies, the efficiency of European policy-making is seriously hampered, and without a constitution there is little hope that this will improve.
Keywords: 330